Evidence of a Causal Relationship Between Vitamin D Status and Risk of Psoriasis From the UK Biobank Study - Zhang, Yan; Jing, Danrong; Zhou, Guowei; Xiao, Yi; Shen, Minxue; Chen, Xiang; Liu, Hong (Frontiers in Nutrition, 2022)
Background Plenty of observational studies suggested that vitamin D concentrations were associated with psoriasis, but the causality of this relationship was elusive. Objective To investigate the causal relationship between vitamin D and psoriasis. Methods Cox proportional hazard model was used to investigate the association between vitamin D status and psoriasis in a prospective cohort study from UK Biobank. Single nucleotide polymorphisms (SNPs) that are strongly associated with circulating 25OHD were constructed as instrumental variables in Mendelian randomization (MR) to determine the causality between vitamin D and psoriasis. Results During a median follow-up of 10.99 years, we identified 2,856 participants with incident psoriasis. The prospective cohort study demonstrated individuals with 25OHD deficiency (< 25 nmol/L) at baseline were associated with approximately 20% increased risk of incident psoriasis in different categories of sex, age, and body mass index (BMI) after adjusting for covariates. The largest effect size was observed in the obese group (BMI > 30 kg/m2), as 25OHD deficiency presented with 30% additional risk of incident psoriasis compared to those with 25OHD > 50 nmol/L (HR = 0.701; 95% CI: 0.583–0.843; p < 0.001). Additionally, 69 independent SNPs associated with circulating 25OHD level were selected for the MR analysis, and the result suggested that genetically predicted one standard deviation (SD) increment in log-transformed 25OHD was associated with 24% decreased risk of psoriasis (OR = 0.76; 95% CI: 0.60–0.98, p = 0.020). Limitations The association of 25OHD and severity of psoriasis could not be estimated in the current study. Conclusion The combined prospective and MR analysis additionally provided evidence that the epidemiologically and genetically determined level of 25OHD conferred an increased risk of psoriasis.